2021
DOI: 10.1177/00307270211045408
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing cassava farmer typologies and their seed sourcing practices to explore opportunities for economically sustainable seed business models in Rwanda

Abstract: The overdependency on local cassava varieties and informal seed sources by farmers in Rwanda has contributed to the spread of cassava viral diseases. The use of improved planting materials made available through formal seed sources, that assure seed quality, is one way to prevent future disease outbreaks. In order to increase the availability of, and farmers access to, such materials there is increasing interest to develop seed business models. This study aims to understand seed sourcing practices of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Our results indicated that the informal system is the primary source of legume seed for the vast majority of smallholders in the region (Mulesa et al 2021 ; Ayenan et al 2017b ; Kilwinger et al 2021 ; Marimo et al 2021 ; McGuire and Sperling 2016 ; Nordhagen and Pascual 2013 ). It is, however, essential to underscore that this scope excludes cash legumes (e.g., soybean and common bean), as their seed supply is primarily controlled by the formal sector and influenced by market demand, government policies, and interest from research institutes.…”
Section: Resultsmentioning
confidence: 66%
“…Our results indicated that the informal system is the primary source of legume seed for the vast majority of smallholders in the region (Mulesa et al 2021 ; Ayenan et al 2017b ; Kilwinger et al 2021 ; Marimo et al 2021 ; McGuire and Sperling 2016 ; Nordhagen and Pascual 2013 ). It is, however, essential to underscore that this scope excludes cash legumes (e.g., soybean and common bean), as their seed supply is primarily controlled by the formal sector and influenced by market demand, government policies, and interest from research institutes.…”
Section: Resultsmentioning
confidence: 66%
“…This could be attributed to unaffordability of the planting material by most farmers as well as lack of sufficient quantities of certified seed material hindering efforts to use certified cassava planting material. There is need for the promotion and adoption of seed business models for sustainable supply of disease-free cassava planting material for farmers (Kilwinger et al, 2021). In addition appropriate incentives need to be implemented to attract more private investors into cassava seed production businesses.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 25 studies referring to this term in the literature review, only 4 had a defini�on of the concept (Table 5), which reflects the risk that the term is being used without a clearly understanding of its roots and meaning. The business model concept has been used to refer to or describe seed delivery systems (Lalani et al 2019;Nagarajan et al 2021;McEwan et al 2021;Mausch et al 2021), allude to private sector, commercial or profit driven business models Kilwinger et al 2021;Shilomboleni et al 2022), explore opportuni�es for private sector business development (Akpo et al 2020;Kilwinger et al 2021), examine business strategies (Mahove, 2019), as well as to iden�fy key issues of exis�ng business models and promote changes for improvement (Long et al 2017;Nagarajan et al 2021). the seed to other smallholder farmers (channels); outsourcing seed produc�on with smallholder farmers as opposed to large companies that produce their seed with large-scale farmers (key partnerships); developing marke�ng and seed technology promo�onal ac�vi�es such as field days and seed fairs jointly with seed growers (key ac�vi�es); and establishing long-term and trustworthy rela�onships with smallholder seed growers (customer rela�onships).…”
Section: Business Models and Their Use In Seed Delivery And Technolog...mentioning
confidence: 99%
“…The business model concept has also been used interchangeably with term «strategy». For instance, Kilwinger et al (2021) suggest the use of nuanced tailored business models that incorporate farmers' diversity and meet farmers' diverse needs and capaci�es. Something that is not clear from their analysis is whether these nuanced tailored business models refer rather to different strategies needed to serve different market segments (farmer typologies) as reflected in their sentence: "the heterogeneity among farmers, their farms, and farming practices creates the risk that a one-size-fits-all strategy or model would favour and appeal to only a specific group of farmers (p.442)".…”
Section: Business Models and Their Use In Seed Delivery And Technolog...mentioning
confidence: 99%